GE_GERICHTE P/8341/2019 vom 21. Februar 2022 - GE Cour de justice (2022)
CLASSEMENT DE LA PROCÉDURE;ADMINISTRATION DES PREUVES;CONTRAINTE(DROIT PÉNAL);BANQUE | CPP.318.al2; CPP.244; CPP.319.al1; CP.181; CP.156; LB.47; CP.321; CP.14